Research and exploration of quality control indicators for nutritional therapy in critically ill patients—a multicenter before-and-after controlled study - Li, Yanhua; Wang, Youquan; Chen, Bin; Zhang, Zhe; Zhang, Dong (Frontiers in Nutrition, 2024)
Objective To evaluate and explore the feasibility of using quality control indicators for nutritional therapy in critically ill patients as quality evaluation criteria. Methods This study focused on intensive care unit (ICU) critically ill patients and conducted a cross-sectional investigation of nutritional therapy quality control indicators (the proportion of patients with application of enteral nutrition pump, nutritional risk assessment rate, the proportion of patients start enteral nutrition within 48 hours, and caloric and protein target achievement rate on 7th day) in 13 hospitals in Jilin Province. After training according to the critical patients nutrition related guidelines and the latest literatures, a second cross-sectional investigation was conducted. Then, analyze the improvement of quality control indicators of the nutritional therapy before and after the training, thus evaluating the feasibility of using these quality control indicators as nutritional therapy quality evaluation criteria in critical patients. Results (1) A total of 631 patients were included before and after training, with a data acquisition rate of 97.3% for enteral nutrition pumps usage and complete data collection for the remaining nutritional risk assessment rate, start enteral nutrition proportion of patients within 48 h, and caloric and protein target achievement rate on 7th day. (2) The nutritional risk assessment rate before and after training was 88.2% vs. 94.8%, with a P-value of 0.003. The proportion of patients start enteral nutrition within 48 h before and after training was 65.1% vs. 75.4%, with a P-value of 0.039; and protein target achievement rate on 7th day before and after training was 64.6% vs. 79.6%, with a p-value of 0.015. These five indicators as quality evaluation criteria are relevant to the current developments in nutritional therapy and consistent with the national conditions of China. The proportion of patients with application of enteral nutrition pump before and after training was 70.1% vs. 79.4%, with a p-value of 0.065, and the caloric target achievement rate on 7th day before and after training was 73.4% vs. 83.9%, with a p-value of 0.062, and there was no statistical difference between the two groups. Conclusion The five quality control indicators for nutritional therapy in critically ill patients are clinically feasible and can be used as quality evaluation criteria for nutritional therapy in critically ill patients.